A mental health needs assessment of children and adolescents in post-conflict Liberia: results from a quantitative key-informant survey. Issue 1 (2nd January 2016) - Borba, Christina P.C.; Ng, Lauren C.; Stevenson, Anne; Vesga-Lopez, Oriana; Harris, Benjamin L.; Parnarouskis, Lindsey; Gray, Deborah A.; Carney, Julia R.; Domínguez, Silvia; Wang, Edward K.S.; Boxill, Ryan; Song, Suzan J.; et al.
Abstract : Between 1989 and 2004, Liberia experienced a devastating civil war that resulted in widespread trauma with almost no mental health infrastructure to help citizens cope. In 2009, the Liberian Ministry of Health and Social Welfare collaborated with researchers from Massachusetts General Hospital to conduct a rapid needs assessment survey in Liberia with local key informants ( n = 171) to examine the impact of war and post-war events on emotional and behavioral problems of, functional limitations of, and appropriate treatment settings for Liberian youth aged 5–22. War exposure and post-conflict sexual violence, poverty, infectious disease and parental death negatively impacted youth mental health. Key informants perceived that youth displayed internalizing and externalizing symptoms and mental health-related functional impairment at home, school, work and in relationships. Medical clinics were identified as the most appropriate setting for mental health services. Youth in Liberia continue to endure the harsh social, economic and material conditions of everyday life in a protracted post-conflict state, and have significant mental health needs. Their observed functional impairment due to mental health issues further limited their access to protective factors such as education, employment and positive social relationships. Results from this study informed Liberia's first post-conflict mental health policy.